2023
DOI: 10.1186/s12981-022-00488-7
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the needs of older people living with HIV (≥ 50 years old) from multiple centres over the world: a descriptive analysis

Abstract: Background Older People Living with HIV (OPWH) combine both aging and HIV-infection features, resulting in ageism, stigma, social isolation, and low quality of life. This context brings up new challenges for healthcare professionals, who now must aid patients with a significant comorbidity burden and polypharmacy treatments. OPWH opinion on their health management is hardly ever considered as a variable to study, though it would help to understand their needs on dissimilar settings. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
(68 reference statements)
1
10
0
Order By: Relevance
“…A recent study surveying 680 participants from 4 different regions around the globe demonstrated very different priorities, quality of life assessments, and psychosocial needs between these locations. 125 …”
Section: Discussion: Are We Doing Enough?mentioning
confidence: 99%
“…A recent study surveying 680 participants from 4 different regions around the globe demonstrated very different priorities, quality of life assessments, and psychosocial needs between these locations. 125 …”
Section: Discussion: Are We Doing Enough?mentioning
confidence: 99%
“…The aging process, coupled with the HIV infection and various health concerns such as liver and kidney deterioration, non-AIDS-related illnesses, geriatric syndromes, and heightened emotional and physical stress, can have a substantial impact on older PWH [5][6][7], resulting in more complex and challenging clinical management. The primary intervention for HIV is ART; however, no specific ART regimen has yet been established for older populations.…”
Section: Introductionmentioning
confidence: 99%
“…For people living with HIV, sexual health and intimate partner relationships are important components of HRQOL and emotional well-being across the life span [2,3]. Although their importance has been increasingly recognized in the literature [4,5], the sexuality of ageing people living with HIV is often considered of little importance when assessing HRQOL, despite evidence that older adults continue to desire romantic relationships, intimacy and sexual activity [6,7]. This would suggest that sexuality, sexual health and sexual desires need to be considered in the assessment of HRQOL.…”
Section: Introductionmentioning
confidence: 99%